The learning effects of different presentations of worked examples on medical students' breaking-bad-news skills: A randomized and blinded field trial. Issue 8 (August 2018) - Schmitz, Felix Michael; Schnabel, Kai Philipp; Bauer, Daniel; Bachmann, Cadja; Woermann, Ulrich; Guttormsen, Sissel
Highlights: Learning effects vary between certain presentations of a given worked example (WE). Studying the WE as text or video equally impact students' breaking-bad-news skills. Yet, students learning from the WE as text neglect unpleasant emotions more often. Skills increase significantly when the video WE is accompanied by contextual hints. Abstract: Objectives: Effective instructional approaches are needed to enable undergraduates to optimally prepare for the limited training time they receive with simulated patients (SPs). This study examines the learning effects of different presentation formats of a worked example on student SP communication. Methods: Sixty-seven fourth-year medical students attending a mandatory communication course participated in this randomized field trial. Prior to the course, they worked through an e-learning module that introduced the SPIKES protocol for delivering bad news to patients. In this module, a single worked example was presented to one group of students in a text version, to a second group in a video version, and to a third group in a video version enriched with text hints denoting the SPIKES steps. Results: The video-with-hints group broke bad news to SPs significantly more appropriately than either of the other groups. Although no further condition-related effects were revealed, students who learned from the text version most frequently (although non-significantly) ignored unpleasant emotions (standardised emotional cues and concerns) expressed by the SPs. Conclusions: The learning effect was strongest when the video-based worked example was accompanied by hints. Practice implications: Video-related learning approaches that embed attention-guiding hints can effectively prepare undergraduates for SP encounters.